From Mistletoe to Anthroposophical Architecture: Medicinal Plants Gardens - Özdamar, Esen Gökçe; Yücel Caymaz, Gökçen Firdevs (Street Art & Urban Creativity, 2022)
This article focuses on the Austrian philosopher, social reformer, and architect Rudolf Steiner’s approach to design, architecture, and nature through its anthroposophical thinking about life developed in the 1920s and its reflections on urban space. The article aims to establish a new relationship between art, design, architecture, and landscape, based on Steiner's approach to life, and to fill the gap in how to look at our artificially constructed environment, especially in urbanized areas. As a medicinal plant, mistletoe is one of the parasitic plants that points to the interplay that Steiner observed throughout life. In this article, the concept of "from mistletoe to architecture" is evaluated as a metaphor and represents the view through the holistic relationship established between architecture, nature, and landscape. From the architectural point of view of mistletoe, the bond between them is understood with a holistic approach in which different disciplines, knowledge, interaction, and living together with plants are intertwined in modern urban spaces. Therefore, how can architecture, landscape architecture, and design practices integrate living and being in today's world? Deriving from this, the article evaluates the close relationship between human beings and plants through the medicinal plant gardens in Istanbul and especially the Zeytinburnu Medicinal Plants Garden.